Evaluation of Severity Score in Patients with Lower Limb and Pelvic Fractures Injured in Motor Vehicle Front-Impact Collisions - Gokalp, Mehmet Ata (Med Sci Monit, 2016)
BACKGROUND: Lower limb and pelvic injuries and fractures occur at a very high incidence in motor vehicle accidents. In this study, the characteristics (e.g., body side, bone location, and fracture severity) of lower limb and pelvic fractures that occurred during front-impact collisions were correlated with the injured patients’ sex, age, and position in the vehicle. MATERIAL/METHODS: We retrospectively evaluated 191 patients (136 males, 55 females) who were injured in motor vehicle accidents, specifically in frontal collisions. RESULTS: This study revealed that most of lower limb and pelvic fractures occurred in males (71.2%; p=.000), 19–36 years old (55.5%; p=.000), small vehicles (86.4%; p=.000), and rear seat passengers (49.2%; p=.000). Fractures most commonly occurred in the left side of the body (46.6%; p=.000) and upper legs (37.7%; p=.000). Severity scores were higher (2.76) in males than females (2.07). No statistically significant was found in severity scores of patients and other personal characteristics and fracture features of patients with lower limb and pelvic fractures who were injured in a vehicle during front-impact collisions (p>0.05). CONCLUSIONS: The results of this study will be useful for the automobile industry, forensics and criminal scientists, and for trauma research studies.